Ghost town : a novel - Perrotta, Tom, 1961- (Scribner, 2026)
"Jimmy Perrini lives in 1970s suburban New Jersey, a few miles from Manhattan, but a world apart. At the end of eighth grade, after tragedy strikes, Jimmy finds himself lost in a fog of grief that alienates him from friends and family, drifting instead into troubling friendships with two older teenagers: one a notorious local burnout with a fast car, an endless supply of weed, and a shaky grasp of reality; the other a smart, eccentric girl, whom Jimmy finds himself drawn to as they become entranced by her Ouija board, which may just offer the only salve to their grief. As a fateful public drama unfolds, Jimmy is torn between the occult beyond and the cold realities of the place he has called home. Narrated by a much older Jimmy, a literary-turned-commercial novelist, Ghost Town reveals how the past haunts the present the way our ghosts are always with us, even when we think we've left them behind."--Provided by publisher.